THE EFFECT OF USING RED BRICK WASTE ON ASPHALT CONCRETE BINDER COURSE MIX - M RIFQI BADRIANSYAH; GALI PRIBADI; INDRIASARI (CV KULTURA DIGITAL MEDIA, 2024)
The number of new road constructions is increasing, with the main focus on the repair of old roads. However, these roads often deteriorate before reaching their intended service life due to excessive vehicle loads, lack of maintenance, and problems with the asphalt mixture. Research on additives to asphalt mixtures, such as red brick waste, is needed to improve the quality and durability of roads. The red brick industry, which is largely traditional, often produces defective products that contribute to the failure rate in brick making. The addition of red brick debris to asphalt is expected to not only improve the quality of the pavement but also offer a low-cost solution to the waste problem. Marshall characteristic analysis on AC-BC mixture using red brick powder as a substitute for fine aggregate with variation 0 or normal produces a stability value of 1202.04 kg, for variation 1 with 20% red brick powder waste replacing sand, produces a stability value of 1074.39 kg, for variation 2 with 40% red brick powder waste replacing sand, produces a stability value of 1021.2 kg, while for variation 3 with 60% red brick powder waste replacing sand, produces a stability value of 914.83 kg. These values ​​meet the 2018 Bina Marga specifications.